A diversity and conservation inventory of the Herpetofauna of the Cuautlapan Valley, Veracruz, Mexico - de La Luz, Nelson M. Ceron; Lemos-Espinal, Julio A.; Smith, Geoffrey R. (Zootaxa, 2016)
We compiled an inventory of the amphibians and reptiles of the Cuautlapan Valley, Veracruz, Mexico based on field surveys and museum and literature records. We found a total of 78 species: 28 amphibians (6 Salamanders and 22 anurans); and 50 reptiles (three turtles, 18 lizards, and 29 snakes). These taxa represent 26 families (eight amphibian families, 18 reptile families) and 60 genera (19 amphibian genera, 41 reptile genera). Two of these species are not native to the area (Rhinoclemmys pulcherrima and Hemidactylus frenatus). According to the IUCN red list, five species are Critically Endangered, two are Endangered, four are Near Threatened, and four are Vulnerable. In the SEMARNAT (Secretaría del Medio Ambiente y Recursos Naturales) listing, one species is Endangered, eight species are Threatened, and 25 are Subject to Special Protection. Even though the Cuautlapan Valley is represented by a relatively small area it hosts a rich diversity of amphibian and reptile species, many of which are at risk and protected under Mexican law. This valley lies between the growing cities of Orizaba and Cordoba which have contributed to habitat degradation threatening the existence of the wildlife that occurs there.